THE SHILUBANA JUDGMENT IN LIGHT OF TRANSFORMATIVE CONSTITUTIONALISM (The Pretoria Student Law Review, 2021)
In this essay I explore Karl Klare’s notion of transformative constitutionalism explored in light of the case of Shilubana.1 Firstly, I define transformative constitutionalism and the circumstances present in the South African Constitution (Constitution) that give its interpretation a post liberal propensity are set out. This is followed by establishing why it is important to dull the distinction between law and politics, and by a consideration of the influence of legal culture when interpreting the law. Thereafter, I give a brief background of Shilubana. I argue that Shilubana was informed by some transformative constitutionalism principles as far as enhancing multiculturalism is concerned although it was limited by the legal culture of Justice Van Der Westhuizen. Lastly, I attempt to show that the final outcome of the case did effect desired social change envisaged through or by the project of transformative constitutionalism.
Keywords: Karl Klare; transformative constitutionalism; Shilubana; South African Constitution; multiculturalism